Compounds from Agathis dammara exert hypoglycaemic activity by enhancing glucose uptake: lignans, terpenes and others - Zhe-Wei Yu; Bang-Ping Cai; Su-Zhi Xie; Yi Zhang; Wen-Hui Wang; Shun-Zhi Liu; Yan-Lin Bin; Qi Chen; Mei-Juan Fang; Rong Qi; Ming-Yu Li; Ying-Kun Qiu (Natural Products and Bioprospecting, 2024)
Abstract In this study, two new kaurane diterpenes (16, 17), together with 12 lignans (1–12), a triterpene (15), and two other compounds (13, 14) were isolated from the woods of Agathis dammara. The structure of the new compound was determined by HR ESIMS and 1D/2D NMR spectroscopy, and its absolute configuration was determined by electronic circular dichroism (ECD) exciton chirality method. Compounds 5, 11, 14 exhibit significant hypoglycaemic activity in zebrafish, and their mechanism of action is to enhance glucose uptake in zebrafish. Graphical Abstract